Prevalence of bovine cysticercosis in slaughtered cattle and knowledge attitudes and practices of cattle farmers in the Matabeleland region of Zimbabwe - Tshuma, Takula (University of Pretoria, 2023)
Dissertation (MSc (Veterinary Science))--University of Pretoria, 2022.